Determinants of Expatriate Adjustment Success. (A Case of International Local Hire in Intel Malaysia, Taiwan and Singapore) - Balkis, Mohamad (2011)
The main objective of this study is to identify the criteria for international local hire's (expatriates) adjustment success in the host site. This is to understand the support and help needed from them for a smooth adjustment process. Present study examines the relationship between all the independent variables, namely expatriate behavior, local co-worker credibility as well as perceived organization support with the dependent variable, adjustment success in the host site. There are three dimensions for expatriate behavior which are, extraversion, help seeking behavior and risk in help seeking. To attain the objectives, a quantitative method was employed and data was collected through questionnaires. A total of 114 questionnaires were distributed to international local hires at Intel Malaysia, Intel Taiwan and Intel Singapore. However only 63 (55%) were received and used for further analysis. The data was analyzed using Pearson Correlation and Multiple Regression. The findings indicated that perceived organization support was the only variable that has significant relationship with expatriate adjustment in the host site while expatriate behavior and perceived organization support do not correlate with expatriate adjustment in the host site. In conclusion, this study revealed that perceived organization support is the important criteria for a successful expatriate adjustment. From the results, this would enable improvement programs such as, buddy system, mentor and mentee as well as revising the relocation process and policies to assist international local hire's adjustment in the host site.